KOLABORASI KEPOLISIAN RESOR KOTA PEKANBARU DAN SATPOL PP DALAM MENANGGULANGI PENJUALAN MINUMAN BERALKOHOL OLEH PEDAGANG GEROBAK MOTOR (ANALISIS KEBIJAKAN KRIMINAL) - Neri Widya Ramailis (SISI LAIN REALITA, 2019)
Considering the rampant phenomenon of the trade in alcoholic beverages that are traded in various places by motorbike peddlers especially along the road in Juanda, Pekanbaru City has the potential to add new criminal problems, for example there are indications of abuse of alcoholic beverage use by the buyer (users) especially children and adolescents whose loss of control from family party. Then, people often go to clubs or nightclubs. When they are having a problem or conflict within themselves, they will tend to do things beyond the limits of normal people's thinking, such as drinking excessive alcoholic drinks to get drunk, causing damage and disturbing public order. Fraudulent traders by trading drinks in any place is a phenomenon of crime that leads to the criminal sphere, if viewed from a criminological perspective this phenomenon falls into the category of crime that can interfere with human survival, leading to the disruption of peace, order and peace in the environment Public.